Genome sequence of Acinetobacter baumannii AC12, a polymyxin-resistant strain isolated from Terengganu, Malaysia - Zarizal, Suhaili (2012)
Acinetobacter baumannii is a major cause of nosocomial infection worldwide- We report the draft genome sequence of A baumannii AC12. a multidrug-resistant nosocomial strain with additional resistance to carbapenems and polymyxin. The genome data will provide insights into the genetic basis of antimicrobial resistance and its adaptive mechanism. 0 2012. American Society for Microbiology.